Intellectual Curiosity or Deception? An Investigation into the Practice of Teaching outside Area of Expertise in Uganda - Namubiru Ssentamu, Proscovia (Makerere Journal of Higher Education, 2017)
Teaching outside one’s area of expertise is increasingly common in higher education institutions (HEIs). Yet institutions and scholars are treating the subject as a taboo. Debate on the subject has been kept hush-hush—citing potential jeopardy to the institutions’ image. In this paper, the authors explore the reasons for the trend. The authors adopted Carl Rogers’ Theory to answer four questions: 1) What drives academicians to teach outside their area of primary expertise? 2) What are the implications of teaching outside one’s area of expertise? 3) What is the performance of those teaching outside their expertise? 4) What strategies are in place to regulate the practice? Data was collected from two HEIs in Uganda. This was done using interviews, students’ evaluations and teaching time-tables. Staff job descriptions and profiles were also analysed. It was concluded that the practice is not affecting quality. Regardless, the paper urges HEIs to be judicious in allowing the practice.
Keywords: Teaching and learning; Quality assurance; Professionalism